STUDY ON HOUSING, FEEDING AND MANAGEMENT RAISING OF SWAMP BUFFALO IN HIGHLAND AREA OF JAYAWIJAYA PAPUA - Dapla, Meos; Supriyantono, Andoyo; Iyai, Deny A. (Proceeding Buffalo International Conference, 2013)
Buffalo in Wamena is a famous ruminant which raise by most people from Toraja. Raising management of the animal is a conventional way due to abundant of natural resources. The research aimed to study on housing, feeding and management raising of swamp buffalo. Research method used was descriptive with study case technique. As a case was farmers who were raising buffalo at Pickhe and Kama district. Data were collected base on interview guided by questionnaire. Eight farmers were gathered to answer the question concerning housing, feeding and management raising of buffalo. Data were analyzed using excel to get mean and standard deviation. Results showed that the farmers did not pay attention in term of reproduction aspect; feeding and drinking. All farmers did not have housing for their buffalos they kept all the animals into ranch which has fences. Due to the raising system farmers did not make any treatment for preventing the disease to the animals.